LGR5 is a Marker of Poor Prognosis in Glioblastoma and is Required for Survival of Brain Cancer Stem‐Like Cells. (30th August 2012) - Nakata, Susumu; Campos, Benito; Bageritz, Josephine; Lorenzo Bermejo, Justo; Becker, Natalia; Engel, Felix; Acker, Till; Momma, Stefan; Herold‐Mende, Christel; Lichter, Peter; Radlwimmer, Bernhard; Goidts, Violaine
Abstract In various types of cancers including glioblastoma, accumulating evidence show the existence of cancer stem‐like cells (CSCs), characterized by stem cell marker expression, capability of differentiation and self‐renewal, and high potential for tumor propagation in vivo. LGR5, whose expression is positively regulated by the Wnt signaling pathway, is a stem cell marker in intestinal mucosa and hair follicle in the skin. As Wnt signaling is also involved in brain development, the function of LGR5 in the maintenance of brain CSCs is to be assessed. Our study showed that the LGR5 transcript level was increased in CSCs. Co‐immunofluorescence staining demonstrated the co‐localization of CD133‐ and LGR5‐positive cells in glioblastoma tissue sections. Functionally, silencing of LGR5 by lentiviral shRNA‐mediated knockdown induced apoptosis in brain CSCs. Moreover, LGR5 depletion led to a downregulation of L1 cell adhesion molecule expression. In line with an important function in glioma tumorigenesis, LGR5 expression increased with glioma progression and correlated with an adverse outcome. Our findings suggest that LGR5 plays a role in maintenance and/or survival of brain CSCs.